Automatically gated image-guided breath-hold IMRT is a fast, precise, and dosimetrically robust treatment for lung cancer patients - Simeonova-Chergou, Anna; Jahnke, Anika; Siebenlist, Kerstin; Stieler, Florian; Mai, Sabine; Boda-Heggemann, Judit; Wenz, Frederik; Lohr, Frank; Jahnke, Lennart (Strahlentherapie und Onkologie, 2016)
Background: High-dose radiotherapy of lung cancer is challenging. Tumors may move by up to 2 cm in craniocaudal and anteroposterior directions as a function of breathing cycle. Tumor displacement increases with treatment time, which consequentially increases the treatment uncertainty. Objective: This study analyzed whether automatically gated cone-beam-CT (CBCT)-controlled intensity modulated fast deep inspiration breath hold (DIBH) stereotactic body radiation therapy (SBRT) in flattening filter free (FFF) technique and normofractionated lung DIBH intensity-modulated radiotherapy (IMRT)/volumetric-modulated arc therapy (VMAT) treatments delivered with a flattening filter can be applied with sufficient accuracy within a clinically acceptable timeslot. Materials and methods: Plans of 34 patients with lung tumors were analyzed. Of these patients, 17 received computer-controlled fast DIBH SBRT with a dose of 60 Gy (5 fractions of 12 Gy or 12 fractions of 5 Gy) in an FFF VMAT technique (FFF-SBRT) every other day and 17 received conventional VMAT with a flattening filter (conv-VMAT) and 2-Gy daily fractional doses (cumulative dose 50-70 Gy).ResultsFFF-SBRT plans required more monitor units (MU) than conv-VMAT plans (2956.6 ± 885.3 MU for 12 Gy/fraction and 1148.7 ± 289.2 MU for 5 Gy/fraction vs. 608.4 ± 157.5 MU for 2 Gy/fraction). Total treatment and net beam-on times were shorter for FFF-SBRT plans than conv-VMAT plans (268.0 ± 74.4 s vs. 330.2 ± 93.6 s and 85.8 ± 25.3 s vs. 117.2 ± 29.6 s, respectively). Total slot time was 13.0 min for FFF-SBRT and 14.0 min for conv-VMAT. All modalities could be delivered accurately despite multiple beam-on/-off cycles and were robust against multiple interruptions. Conclusion: Automatically gated CBCT-controlled fast DIBH SBRT in VMAT FFF technique and normofractionated lung DIBH VMAT can be applied with a low number of breath-holds in a short timeslot, with excellent dosimetric accuracy. In clinical routine, these approaches combine optimally reduced lung tissue irradiation with maximal delivery precision for patients with small and larger lung tumors.